Proximate Analysis of Holy Quran Recitations on Physiological, Psychological, and Neural Functioning in Muslims - Muhammad Muqarrab Latif; Asif Hussain Bhatti (UIN Sunan Gunung Djati Bandung, 2024)
In contemporary times, the increasing susceptibility to psychological disorders has prompted researchers to explore diverse approaches, encompassing both pharmacological and non-pharmacological interventions. A notable trend among scholars involves investigating the efficacy of religious therapy, particularly the recitation of the Holy Quran, as a means to address these health issues. This review systematically assesses studies examining the impact of Holy Quran recitation on cardiac and mental performance, as well as psychological disorders such as anxiety, stress, depression, and labor pain. The cultural significance of the Holy Quran in Muslim societies underscores the relevance of this intervention. Through a systematic evaluation of relevant studies, a positive impact of Holy Quran recitation emerges, demonstrating improvements in cardiac and mental performance, as well as the alleviation of anxiety, stress, depression, and labor pain. Across all studies, statistically significant differences were noted between groups employing Holy Quran recitation therapy and those utilizing alternative interventions, supporting its confident use as a non-pharmacological remedy for health problems. While the positive effects are evident, implementation requires a robust methodology, emphasizing the need to delineate specific surahs for different diseases. This review contributes to the growing evidence supporting Holy Quran recitation therapy as a viable non-pharmacological intervention, highlighting the importance of future research to optimize its therapeutic application.